Exposure to nature gardens has time-dependent associations with mood improvements for people with mid- and late-stage dementia: Innovative practice. (July 2018) - White, Piran CL; Wyatt, Jonathan; Chalfont, Garuth; Bland, J Martin; Neale, Christopher; Trepel, Dominic; Graham, Hilary
Exposure to green space and nature has a potential role to play in the care of people with dementia, with possible benefits including improved mood and slower disease progression. In this observational study at a dementia care facility in the UK, we used carer-assessed measures to evaluate change in mood of residents with mid- to late-stage dementia following exposure to a nature garden. We found that exposure to nature was associated with a beneficial change in patient mood. There was a non-linear relationship between time spent outdoors and mood outcome. Improvements in patient mood were associated with relatively short duration exposures to nature, and no additional measureable increases in mood were found with exposures beyond 80–90 minutes duration. Whilst further investigation is required before causality can be determined, these results raise important questions for policy about the integration of outdoor space into the design of dementia care facilities and programmes.